Novel order parameter to describe the critical behavior of Ising spin glass models - Romá, Federico José (2006)
A novel order parameter Φ for spin glasses is defined based on topological criteria and with a clear physical interpretation. Φ is first investigated for well known magnetic systems and then applied to the Edwards-Anderson ±J model on a square lattice, comparing its properties with the usual q order parameter. Finite size scaling procedures are performed. Results and analyses based on Φ confirm a zero temperature phase transition and allow to identify the low temperature phase. The advantages of Φ are brought out and its physical meaning is established.